2020
DOI: 10.1007/s10787-020-00773-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Therapeutic Potential of NF-kappa-B Pathway in Severe COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) pandemic has affected health care systems worldwide. Severe presentations of COVID-19 such as severe pneumonia and acute respiratory distress syndrome (ARDS) have been associated with the post-viral activation and release of cytokine/chemokines which leads to a “cytokine storm” causing inflammatory response and destruction, mainly affecting the lungs. COVID-19 activation of transcription factor, NF-kappa B (NF-κB) in various cells such as macrophages of lung, liver, kidney, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
237
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(245 citation statements)
references
References 93 publications
8
237
0
Order By: Relevance
“…COVID-19 patients with severe COVID-19 displayed the uncontrolled NF-Brelated cytokine release syndrome (CRS), which is responsible for the poor prognosis and multiorgan defects (8). Thus, the pharmacological blockade of the NF-B signaling pathway can strongly represent a potential therapeutic consideration to attenuate COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients with severe COVID-19 displayed the uncontrolled NF-Brelated cytokine release syndrome (CRS), which is responsible for the poor prognosis and multiorgan defects (8). Thus, the pharmacological blockade of the NF-B signaling pathway can strongly represent a potential therapeutic consideration to attenuate COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating sIL-6Rα can bind its ligand IL-6, causing the intracellular activation of the JAK/STAT3 pathway, which is a well-known trigger of NF-κB [ 73 ]. NF-κB is among the most important checkpoints involved in COVID-19-related proinflammatory events [ 62 , 74 ] and it is a pivotal protein complex involved in immune regulation [ 75 ].…”
Section: Cytokine Stormmentioning
confidence: 99%
“…Another example is the interaction of SIRTs with key transcription factors, such as NF-κB and FOXO1 [ 152 , 153 , 154 , 155 ]. The connection and crosstalk between NF-κB and SIRT1 in the regulation of inflammation (see Figure 8 ) and metabolic disorders have been investigated thoroughly by Kauppinen et al [ 152 ].…”
Section: Sirts As Emerging Antiviral Targetsmentioning
confidence: 99%
“…The inhibition of SIRT1 disrupts oxidative energy metabolism and stimulates the NF-κB-induced inflammatory responses. Hariharan et al, have reported that the SARS-CoV-2 components induce the activation of NF-κB in different cells, leading to the production of various chemokines (chemokines ‘storm’) [ 153 ] (see Figure 8 ).…”
Section: Sirts As Emerging Antiviral Targetsmentioning
confidence: 99%